Digging deep to compete: vertical integration, product market competition and prices - McGowan, Danny (Wiley, 2017)
This article establishes a causal effect of product market competition on vertical integration. I exploit a hitherto unexplored natural experiment in the US coal mining industry and a unique mine-level organizational data set. Following an exogenous increase in product market competition the incidence of vertical integration fell by 33% within the treatment group relative to the counterfactual. I find novel evidence that transition to the lower degree of vertical integration is driven by competition reducing market prices by 32% which decreased the incentive to conduct vertical mergers. I discuss several possible interpretations of these changes.